2017
DOI: 10.1063/1.5002573
|View full text |Cite
|
Sign up to set email alerts
|

Photo-spin voltaic effect and photo-magnetoresistance in proximized platinum

Abstract: Spin orbit coupling in heavy metals allows conversion of unpolarized light into an open-circuit voltage. We experimentally prove that this photo-spin voltaic effect is due to photo-excitation of carriers in the proximized layer and can exist for light in the visible range. While carrying out the experiment, we discovered that, in closed-circuit conditions, the anisotropic magnetoresistance of the proximized metal is a function of the light intensity. We name this effect photomagnetoresistance. A magneto-transp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Ellsworth et al [13] measured the PSV voltage in the infrared region in the Pt layer proximized by YIG. Similarly, Li and Ruotolo [2] experimentally showed that the PSV effect also existed in the visible range. In addition, they demonstrated that the AMR of the proximized layer is light-dependent.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Ellsworth et al [13] measured the PSV voltage in the infrared region in the Pt layer proximized by YIG. Similarly, Li and Ruotolo [2] experimentally showed that the PSV effect also existed in the visible range. In addition, they demonstrated that the AMR of the proximized layer is light-dependent.…”
Section: Introductionmentioning
confidence: 77%
“…In ultra-thin PtMn films, the Nèel temperature was measured to be below room temperature. Yet, like ultra-thin Pt films on YIG, a proximity effect exists near the interface and a magnetization arises in the metal over depths of ∼0.5 nm [2].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations